Penanganan Keluhan Tamu oleh Karyawan Front Office di Grand Rocky Hotel Bukittinggi - Syafriani, Oza; Yuliana, Yuliana; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research was motivated by complaints that are made by the guest to the front office employee regarding low responsive and low empathie by the guests, the absence of confirmation and clarification of issues that the guest had given to the employee. The research uses consisted of four indicators witch are hear them out, emphatize, apologize, and taking action and follow up. The research use descriptive study with qualitative data, and collected using Method interviews, observation, and documentation, for the sample use snowball sampling. These results indicate that the handling of guest complaints by front office employees at Grand Rocky Hotel Bukittinggi using the HEAT are as follows: 1)the front office employees had conducted hear them out by listening carefully, respect and respond actively and understand guests,2)the front office employee had conducted emphatize to guests 3)the front office employee had conducted apologize and humble to guest 4)the front office employee had conducted taking action by clarified, give a solutions, approval and take action and follow-up. Key Word : Hear them out, emphatize, apologize, taking action and follow up.